Synthesis, Characterization and Theoretical Anti-Corrosion Study for Substitute Thiazole Contained Cyclobutane Ring - Aktaş, Arzu Etkeser; Omer, Rebaz; Koparır, Metin (Niyazi BULUT, 2022)
This study was synthesized: 1-(4-(3-methyl-3-phenylcyclobutyl)thiazol-2-yl)-3-phenylthiourea and 1-(4-chlorophenyl)-3-(4-(3-methyl-3-phenylcyclobutyl)thiazol-2-yl)thiourea. Fourier-Transform Infrared (FT-IR) spectroscopy and Nuclear Magnetic Resonance (NMR) were used to characterize the molecular formula. Theoretical vibration was computed with Gaussian 09W software, and corrosion inhibiting activity was computed with quantum chemical calculations. Furthermore, the GaussView 5.0 package was used on the B3LYP/6-311G(d,p) method to calculate the energy of the highest occupied molecular orbital (EHOMO), the energy of the lower occupied molecular orbital, energy gap (?E = ELUMO - EHOMO), the dipole moment (µ), and the percent of transmitted electrons (?N). Other molecular properties such as hardness (?), softness (?), and electronegativity (?) were calculated based on the results of inhibitor activity. The corrosion inhibiting activities of the derivatives were predicted using quantum chemical calculations. As a result, the corrosion inhibitor behavior can be predicted without the need for an experimental study. The results show a strong relationship between organic-based corrosion inhibitors and the process's quantum chemical parameters.
Keywords: Chemical Engineering; Kimya Mühendisliği